Conocybe karakensis sp. nov. (Bolbitiaceae, Agaricales) from Pakistan - Ullah, Tauseef; Ullah, Khetab; Saba, Malka; Shah, Fahim Hussain (Phytotaxa, 2023)
This research presents a new species in the genus Conocybe collected from the tropical semi-arid District Karak, Khyber Pakhtunkhwa, Pakistan. Morphological features, and DNA barcoding marker (ITS-region) were used for the systematic placement of Conocybe karakensis. The present species is characterized by having a medium-sized fruiting body, semi-ovate, orange-colored pileus, free, spaced, and regular lamellae with a central, light brown stipe, thick-walled, oblong basidiospores and clavate shaped, tetra-sterigamtic basidia. Molecularly, initial Blast analysis and the phylogenetic analyses showed that Pakistani collection is closely related to Conocybe velutipes. In the phylogenetic tree, ITS sequences of Pakistani collection clustered in a separate clade sister to Conocybe velutipes. This study provides full description, illustrations, and phylogenetic analyses to distinguish this novel taxon from its closest relatives.